Formation and evolution of macro inclusions in IF steels during continuous casting. (26th November 2017) - Deng, Xiaoxuan; Ji, Chenxi; Cui, Yang; Tian, Zhihong; Yin, Xue; Shao, Xiaojing; Yang, Yindong; McLean, Alex
Abstract : The evolution of macro inclusions during continuous casting was investigated by large-area inclusion characterization using ASPEX and analysis of nozzle blockage deposits. Six kinds of inclusions over 5 μm were observed in samples taken from the tundish and the slabs: single alumina particles, alumina dendrites, refractory-related alumina, alumina associated with bubbles, alumina clusters and Al–Ti complex oxides. By examining the morphology of the nozzle blockage deposit, it was concluded that the refractory-related alumina in the slabs came from the decarburization layer washed away by the steel stream. Some of the alumina clusters that came from the nozzle blockage deposit dislodged by the steel flow, were formed by the agglomeration and sintering of 5–20 μm inclusions that were carried over from the tundish. Two kinds of Al–Ti oxides were found in the tundish, and their evolution mechanisms during the casting process were proposed.